General Principles for the Formation of Natural-Scientific Pictures of the World in Little Schoolchildren - Kosimova Gavkhar Islamovna (Genius Publishing Group, 2022)
In the article, the process of cognition of the world by younger schoolchildren is associated with social cognition. In addition to the general laws of cognition, it is important for younger students to take into account the specifics of perception and attention, imagination, and thinking.
Keywords: science; universe; concept; perception